(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the processes of struggle for power in Movarounnahr in 1358-1370, their causes and consequences based on historical sources. The views of Ghiyasuddin Ali, Nizamuddin Shami, Muiniddin Natanzi, Sharafuddin Ali Yazdi, Fasih Khawafi and Ibn Arabshah on the events that happened in these years were studied on the basis of comparative, critical and historical analysis.